Pengaruh Kombinasi Akupunktur dan Formula Bai Zi Yang Xin Tang Pada Klien Insomnia Sindrom Disharmoni Jantung dan Ginjal di Yayasan Sosial Dharma Warga Surabaya - Jessi Suryani Setiawan; Anindini Winda Amalia; Lim Lia Harumiaty (JURNAL FISIOTERAPI DAN ILMU KESEHATAN SISTHANA, 2023)
Insomnia is one of the most common diseases in modern society, with its characteristics being difficulty sleeping at night or failure to maintain effective sleep after sleep. Conventional treatments for existing insomnia have undesirable effects when used for a long time. Treatment with acupuncture and herbs can be used as an alternative and complementary therapy in the treatment of insomnia. Research purposes to determine the effect of a combination of acupuncture and herbal therapy Bai Zi Yang Xin Tang on client insomnia with heart and kidney disharmony syndrome at Yayasan Dharma Warga Surabaya. Research methods is one group pre-test and post-test design. Respondents in the study amounted to 14 people received acupuncture therapy at point (Feng Chi, An Mian, Bai Hui, Si Shen Cong, Shen Men, Nei Guan, Zu San Li, San Yin Jiao, Tai Xi, Tai Chong) and consumed Bai Zi Yang Xin Tang. The average length of sleep for respondents before therapy was 3.75 Â± 0.47 hours and after therapy 6.0 Â± 0.65 hours (p < 0.05). The combination of acupuncture and Bai Zi Yang Xin Tang for insomnia with heart and kidney disharmony syndrome can increase the patient's sleep duration after therapy.